2016
DOI: 10.2320/matertrans.maw201604
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Hydrogen Solubility and Diffusivity of V–Fe Alloys toward the Design of Hydrogen Permeable Membrane for Low Operative Temperature

Abstract: A concept for alloy design of hydrogen permeable membrane with high hydrogen permeability and long-term durability has been proposed in view of the PCT factor, f PCT , and the ductile-to-brittle transition hydrogen concentration, DBTC. As an example, V-10mol%Fe alloy has been designed for low operative temperature, which exhibits excellent and stable hydrogen permeability for at least 1000 hours at 573 K without brittle fracture.In addition, the alloying effects of iron on the hydriding property and the hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 26 publications
0
26
0
1
Order By: Relevance
“…Suzuki et al showed that the hydrogen diffusivity (B) and solubility (f PCT ), which contribute to the hydrogen flux (J) directly, can be separately analyzed using Equation (18), as stated in Section 3. The validity of Equation (18) has been confirmed by the permeation tests for Pd-, Nb-, and V-based alloy membranes [26][27][28][29][30][31][32]. For example, the changes in the hydrogen flux through a pure Nb membrane is measured at 400 • C with different pressure conditions.…”
Section: Consistent Description Of Hydrogen Permeation Based On Hydromentioning
confidence: 77%
See 4 more Smart Citations
“…Suzuki et al showed that the hydrogen diffusivity (B) and solubility (f PCT ), which contribute to the hydrogen flux (J) directly, can be separately analyzed using Equation (18), as stated in Section 3. The validity of Equation (18) has been confirmed by the permeation tests for Pd-, Nb-, and V-based alloy membranes [26][27][28][29][30][31][32]. For example, the changes in the hydrogen flux through a pure Nb membrane is measured at 400 • C with different pressure conditions.…”
Section: Consistent Description Of Hydrogen Permeation Based On Hydromentioning
confidence: 77%
“…Membranes 2020, 10, x FOR PEER REVIEW 3 of 21 recently in Pd-Ag alloy membranes [27], and (d) alloy design of V-based alloy membranes with high hydrogen permeability and strong resistance to hydrogen embrittlement [28].…”
Section: Pressure-dependent Hydrogen Permeation Coefficientmentioning
confidence: 99%
See 3 more Smart Citations